Literature, History, Periodization, and the Pleasures of the Latin Literary History of Late Antiquity - Shanzer, Danuta (History compass, 2009)
This survey aims to look back on, and to serve as an invitation to, the study of the Latin literature of Late Antiquity. While Late Antiquity has now emerged and been validated as an important subject for historians, the same cannot be said for philologists, literary historians, and literary critics. Paradigms of decadence, degeneration, and decline still reign in the minds of many classicists (from whose ranks many ‘late antiques’ will ultimately be recruited), while many historians who come to Late Antiquity from the Middle Ages will remain just that, namely historians, and may not have the chance to acquire the linguistic formation to study Late Antique texts closely; perhaps not even the will to do so, for the study of medieval history through literary texts (as opposed to documents) is comparatively recent.1 The classical canon is restrictive, excluding, as it does, Christian and Jewish texts. The available larger scale literary histories may not be doing much to make scholars want to read texts from the late 2nd through the 7th century. They range from the dismissive acceleration through ‘fly-over’ territory to the learned, objective, exhaustive, but dry. From the early 20th century the effete and decadent Des Esseintes's Late Latin reading list in Huysmans's A rebours still seems rather more stimulating. A much broader, but gradual approach, acknowledging that one cannot do everything, will ultimately be most constructive. Late Antiquity has an enormous amount of new and emerging material for study as well as great and complicated old problems to contemplate. Special pleasures include the study of the literary history of specific provinces, learning to work with hagiography, reading ‘substandard’ Latin (including papyrological and epigraphic texts), contemplating the long trajectory of the evolution from Latin to Romance, reading authors with highly distinctive voices, learning to love exegesis, and more. Self-identification as ‘textual’ rather than purely ‘literary’ specialists is particularly empowering.